Common mechanisms explain nitrogen-dependent growth of Arctic shrubs over three decades despite heterogeneous trends and declines in soil nitrogen availability - Martin, Andrew C (The New phytologist, 2022)
© 2021 The Authors. New Phytologist © 2021 New Phytologist Foundation.